In vitro and in vivo evaluation of structurally-controlled silk fibroin coatings for orthopedic infection and in-situ osteogenesis. (15th October 2020) - Wenhao, Zhou; Zhang, Teng; Yan, Jianglong; Li, QiYao; Xiong, Panpan; Li, Yangyang; Cheng, Yan; Zheng, Yufeng
Abstract: Biomedical device-associated infections (BAI) and osteosynthesis are two main complications following the orthopedic implant surgery, especially while infecting bacteria form a mature biofilm, which can protect the organisms from the host immune system and antibiotic therapy. Comparing with the single antibiotics therapeutic method, the combination of silver nanoparticles (AgNPs) and conventional antibiotics exert a high level of antibacterial activity. Nevertheless, one major issue that extremely restricts the potential application of AgNP/antiviotics is the uncontrolled release. Moreover, the lack of osteogenic ability may cause the osteosynthesis. Thus, herein we fabricated a structure-controlled drug-loaded silk fibroin (SF) coating that can achieve the size and release control of AgNPs and high efficient osteogenesis. Three comparative SF-based coatings were fabricated: α-structured coating (α-helices 32.7%, ), m-structured coating (β-sheets 28.3%) and β-structured coating (β-sheets 41%). Owning to the high content of α-helices structure and small AgNPs (20 nm), α-structured coating displayed better protein adsorption and hydrophilicity, as well as pH-dependent and long-lasting antibacterial performance. In vitro studies demonstrated that α coating showed biocompatibility (cellular attachment, spreading and proliferation), high ALP expression, collagen secretion and calcium mineralization. Moreover, after one month subcutaneous implantation in vivo, α-structured coating elicited minimal, comparable inflammatory response. Additionally, in a rabbit femoral defect model, α-structured coating displayed a significant improvement on the generation of new-born bone and bonding between the new bone and the tissue, implying a rapid and durable osteointegration. Expectedly, this optimized structure-controlled SF-based coating can be an alternative and prospective solution for the current challenges in orthopedics. Statement of Significance: In this study, an AgNPs/Gentamycin-loaded structured-controlled silk fibroin coatings were constructed on Ti implant's surface to guarantee the success of implantation even in the face of bacterial infection. In comparison, the α-structured coating had the lowest content of β-sheets structure (19.0%) and the smallest particle size of AgNPs (~ 20 nm), and owned pH-responsive characteristic due to reversible α-helices structural. Thanks to pH-responsive release of Ag +, the α-structure coating could effectively inhibit adhesive bacteria and kill planktonic bacteria by releasing a large amount of reactive oxygen radicals. Through in vitro biological results (cell proliferation, differentiation and osteogenic gene expression) and in vivo rabbit femur implantation results, the α-structure coating had good biocompatible and osteogenic properties. Graphical abstract: Image, graphical abstract